İpotek konusu taşınmazın anonim şirketlere sermaye olarak getirilmesi ve ayni sermayeye yüksek değer biçilmesi ihtimalinde gerçek değeri aşan sermaye borcundan sorumluluk - KARAMAN COŞGUN, ÖZLEM (My University, 2022)
Anonim şirketler sermaye şirketleridir. Sermayenin korunması ilkesi mevcuttur. Bu sebeple bazı malvarlığı unsurlarının sermaye olarak konulması yasaklanmıştır. Üzerinde sınırlı ayni bir hak bulunan malvarlığı unsurları da bu yasak kapsamındadır. Ancak uygulamada ipotek konusu taşınmazların sermaye olarak getirilmesi ile ilgili tartışmalar yaşanmıştır. Taşınmaza mahkemece değer biçilmesi sırasında ipoteğin dikkate alınması önerilmiştir. İpotek tesisine sebep olan alacağın taşınmazın değerinden düşülebileceği söylenmiştir. Taşınmazın sermaye olarak konulacağı şirketin borcu için ipotek verilmiş olması tereddüt yaratmıştır. Ayni sermayenin gerçekte olduğundan yüksek bir değerle anonim şirkete hhüdünden kimin sorumlu olduğu da tereddüt oluşturan bir diğer konudur. Gerçek değeri aşan kısmın nakden ödenmesinin mümkün olup olmadığı da tartışmalıdır. Bu kapsamda ayni sermayenin gerçek değerini aşan sermaye taahhüdünün sermayenin azaltılması işlemine konu yapılması görüşü ileri sürülmüştür. Çalışmada uygulama ve doktrinde tartışmalara yol açan bu hususlar ele alınacak, çözüm yolları aranacaktır.

Joint stock companies are companies with share capital. There is the principle of conservation of capital. For this reason, it is prohibited to put some sorts of assets as capital. Assets on which there are limited real rights in rem are also within the scope of this prohibition. However, in practice, there have been discussions about bringing the hypothecated immovable as capital. It has been suggested that the mortgage be taken into account during the appraisal of the immovable by the court. It has been argued that the receivable that caused the hypothecation can be deducted from the value of the immovable. The fact that a mortgage was given for the debt of the company to which the immovable will be placed as capital has created debates. In the event that the capital in kind is brought to the joint stock company with a higher value than it actually is, who shall be responsible for the capital commitment exceeding the actual value is another issue that creates discussions. It is also debatable whether it is possible to pay the portion exceeding the real value in cash. In this context, it has been suggested that the capital commitment exceeding the real value of the in-kind capital should be subject to the capital reduction process. In this study, these issues that cause debates in practice and doctrine will be discussed and solutions will be sought
Liability in joint stock companies for capital debt exceeding the real value, in case of bringing the immovable subject to hypothec as capital and assessing a higher value for the capital in kind
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Ticaret Hukuku; Social Sciences and Humanities; Law; Commercial Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Anonim Şirket; Sermaye; Ayni Sermaye; İpotek; Gerçek Değer; Sermayenin Ödenmesi; Sermaye Azaltımı; Joint Stock Company; Capital; Capital in Kind; Mortgage; Real Value; Payment of Capital; Capital Reduction